Human rights and the image of God - Ruston, Roger, autor (SCM Press, 2004)
Offers a distinctive contribution that is breaking new ground...I think this would be an excellent resource for undergraduate courses and for postgraduate studies. I would definitely recommend it." Dr Tina Beattie, Senior Lecturer, University of Surrey Human Rights and the Image of God is a critical analysis of the relationship between Christian theology and human rights. Written in a lucid and accessible style, this is an excellent resource for students arid academics interested in theology, human rights and the historical background to contemporary ethical debates. The development of the idea of human rights in western society and politics is closely followed, as are the conflicts and debates associated with the idea of human rights.The author surveys the ways in which this development has been closely related to the development of a just war theory. Roger Ruston is a theologian who worked closely on the Dominican Justice and Peace Commission, and for the Christendom Trust.